3(1+2)
3+6
9 ( the answer is nine)
first you divide six and two then use the distributive property to multiply three and one and three and two, then add three and six to get nine.
Answer:
Choice A
Step-by-step explanation:
(4m^5n^2/m^2n)^3
dividing exponents = subtraction
(4m^3n)^3
4^3 = 64
(m^3 )^3 = m^3x3 = m^9
64m^9n^3
X^2+5x=2
you then solve by completing the square using the formula (b/2)^2 in order to create the new term. Solve for x by using this term to complete the square.
Your answer is then
x=-5/2+-√33/2
Answer:
on a graph you do rise over run. find a point that falls on an intersecting line and count how many blocks up and over it is to the next point on a line Hope this helped
Answer: The value of
is
.
Step-by-step explanation:
Given: ![f(x) = 4x^2 \text { and } g(x) = x+1](https://tex.z-dn.net/?f=f%28x%29%20%3D%204x%5E2%20%5Ctext%20%7B%20and%20%7D%20g%28x%29%20%3D%20x%2B1)
To find: ![(f_\circ g)(x)](https://tex.z-dn.net/?f=%28f_%5Ccirc%20g%29%28x%29)
As we know it is composition function which means that g(x) function is in f(x) function.
So we have
![(f_\circ g) (x) = f[g(x)]](https://tex.z-dn.net/?f=%28f_%5Ccirc%20g%29%20%28x%29%20%3D%20%20f%5Bg%28x%29%5D)
![\Rightarrow( f_\circ g)(x)= f(g(x)) = 4(g(x))^2](https://tex.z-dn.net/?f=%5CRightarrow%28%20f_%5Ccirc%20g%29%28x%29%3D%20f%28g%28x%29%29%20%3D%204%28g%28x%29%29%5E2)
Now substitute the value of g(x) we get
![(f_\circ g)(x)= 4(x+1)^2](https://tex.z-dn.net/?f=%28f_%5Ccirc%20g%29%28x%29%3D%204%28x%2B1%29%5E2)
Hence, the value of
is
.